Pathophysiology and fate of hepatocytes in a mouse model of mitochondrial hepatopathies. Issue 2 (19th October 2007) - Diaz, F; Garcia, S; Hernandez, D; Regev, A; Rebelo, A; Oca-Cossio, J; Moraes, C T
Abstract : Background: Although oxidative phosphorylation defects can affect the liver, these conditions are poorly understood, partially because of the lack of animal models. Aims: To create and characterise the pathophysiology of mitochondrial hepatopathies in a mouse model. Methods: A mouse model of mitochondrial hepatopathies was created by the conditional liver knockout (KO) of the COX10 gene, which is required for cytochrome c oxidase (COX) function. The onset and progression of biochemical, molecular and clinical phenotypes were analysed in several groups of animals, mostly at postnatal days 23, 56, 78 and 155. Results: Biochemical and histochemical analysis of liver samples from 23–56-day-old KO mice showed liver dysfunction, a severe COX deficiency, marked mitochondrial proliferation and lipid accumulation. Despite these defects, the COX-deficient hepatocytes were not immediately eliminated, and apoptosis followed by liver regeneration could be observed only at age 78 days. Hepatocytes from 56–78-day-old KO mice survived despite very low COX activity but showed a progressive depletion of glycogen stores. In most animals, hepatocytes that escaped COX10 ablation were able to proliferate and completely regenerate the liver between days 78 and 155. Conclusions: The results showed that when faced with a severe oxidative phosphorylation defect, hepatocytes in vivo can rely on glycolysis/glycogenolysis for their bioenergetic needs for relatively long periods. Ultimately, defective hepatocytes undergo apoptosis and are replaced by COX-positive cells first observed in the perivascular regions.